Facilitators and barriers of using digital technology for the management of diabetic foot ulcers : a qualitative systematic review - Foong, Hui Foh (2022)
The use of digital technology has been shown to be effective in managing chronic conditions. Telemedicine and mobile application are two common applications of digital technology in managing diabetic foot ulcers (DFU). The facilitators and barriers of using it for DFU management are yet to be explored. This is a qualitative systematic review. Five bibliography databases and grey literature sources were searched (2000-2019). Two reviewers independently screened the citations, extracted the data, assessed the quality of the included studies, and performed thematic synthesis. Three studies on patients and five studies on healthcare practitioners (HCPs) were included. Two studies focused on the use of mobile applications and six on telemedicine. In studies on patients, four analytical themes were generated: the relationships with HCPs; the attitude towards the usage of digital technology; the role of wound image taking; and impact of digital technology on DFU care, encompassing 15 facilitators (eg, enabling community support, improving wound care knowledge) and 12 barriers (eg, lack of technological savviness, difficulty reading on smartphones). Three analytical themes were generated from studies on HCPs: the impact of digital technology on HCPs; the role of digital technology in DFU care; and organisation of DFU care delivery, encompassing 17 facilitators (eg, adequate wound care training, digital technology enables holistic care) and 16 barriers (eg, lack of multidisciplinary approach in caring for DFU, lack of direct contact in care provision). Patients and HCPs reported various barriers and facilitators relating to different aspects of using digital technology in DFU management. Our findings can help inform future research as well as the adoption of digital technology in DFU management.